PERANCANGAN STRATEGI BAURAN PEMASARAN UNTUK MENINGKATKAN KEPUASAN DAN LOYALITAS NASABAH PEMBIAYAAN UMRAH - Hendra Kurniawan; Arif Satria; Gendut Suprayitno (School of Business, Bogor Agricultural University (SB-IPB), 2016)
A high level of interest among Indonesians in performing Umrah, a religious tourism, creates the opportunity for banking industries, especially XYZ Sharia bank branch which provides Umrah financing services for the Indonesian Muslim community. The objectives of this study were 1) to analyze the influence of mixed marketing on customer loyalty of XYZ Sharia Bank branch; 2) to analyze the influences of the marketing mix to customer satisfaction of XYZ Sharia Bank branch; 3) to analyze the influence of customer satisfaction on customer loyalty of XYZ Sharia Bank branch; 4) to formulate a marketing strategy to increase customer loyalty of XYZ Sharia Bank branch. This study was conducted using a descriptive method through a case study approach. The data were collected through questionnaires with non-probability sampling technique by using a convenience sampling method. The data were analyzed by using Structural Equation Modeling based on partial least square (PLS-SEM). The PLS SEM analysis results indicated that the mixed marketing is influential on customer satisfaction of XYZ Sharia Bank branch with the influential dimensions of products, prices, employees and processes. Besides, mixed marketing also is significantly influential on customer loyalty of XYZ Sharia Bank branch with the influential dimensions of products, prices, employees, physical evidence and processes. The results of the analysis using ANP demonstrated that implementing cooperation with various travels and Umrah Travel Association in Indonesia is the priority key to improve the marketing of Umrah financial products in Syariah Bank branch by the weight score of 56,03%.Keywords: ANP, mixed marketing, consumer satisfaction, consumer loyalty, Structural Equation Modelling (SEM)-PLS